Willingness of healthcare professionals in China to continue participating in and recommend telemedicine post COVID-19 pandemic - Weiyi Wang; Xianying He; Xu Zhang; Yuntian Chu; Chenchen Li; Baozhan Chen; Jie Zhao (Scientific Reports)
Abstract Sustained engagement and promotion by healthcare professionals are essential for the advancement of telemedicine. Post coronavirus disease 2019 (COVID-19) pandemic, the preference for in-person care highlights the need for research on healthcare professionals’ sustained telemedicine attitudes. This study assessed healthcare professionals’ continued willingness to participate in and recommend telemedicine post-pandemic and identified factors influencing their decisions. From September to October 2023, a cross-sectional study was conducted among 560 healthcare professionals, with samples recruited from 230 hospitals across 11 provinces in China using a multi-stage sampling method. Overall, 518 (92.5%) of 560 respondents expressed their willingness to continue participating in telemedicine, and nearly all respondents (93.5%) displayed a willingness to recommend telemedicine to those in need. The results showed that perceived usefulness, subjective norms, patient coverage, and satisfaction were positively associated with healthcare professionals’ willingness to continue participating in and recommend telemedicine. Satisfaction and subjective norms play a partial mediating role in the effect of usefulness on willingness to continue participating in and recommend telemedicine. Patient coverage partially mediates relationship between usefulness and willingness to recommend telemedicine. Chinese healthcare professionals exhibited a generally high level of willingness to continue participating in and to recommend telemedicine. To further enhance this willingness, it is essential to improve their perceptions of telemedicine’s usefulness, increase their satisfaction with the technology, and emphasize the roles of subjective norms. Moreover, broadening patient access to telemedicine services will be crucial in promoting healthcare professionals’ recommendations.